2023
DOI: 10.21203/rs.3.rs-2559419/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning-based prognostic modeling of lysosome-related genes for predicting prognosis and immune status of patients with hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths worldwide, and lysosomes play an important role in cancer progression as organelles that break down biomolecules such as proteins, nucleic acids, and polysaccharides; however, the molecular mechanisms of lysosome-related genes in hepatocellular carcinoma are not fully understood. Methods:We downloaded hepatocellular carcinoma datasets from the Cancer Genome Atlas(TCGA) and the Gene Expression Omnibus (GEO) as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have indicated that lysosomal-related genes may serve as potential targets for cancer therapy 14,16,41 . However, the clinical relevance of lysosomal-related genes in the diagnosis and treatment of primary liver cancer has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that lysosomal-related genes may serve as potential targets for cancer therapy 14,16,41 . However, the clinical relevance of lysosomal-related genes in the diagnosis and treatment of primary liver cancer has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed that all 8 model genes play a crucial role in the progression and development of tumors through the regulation of lysosomal-related pathways. Recently, a prognostic model of related lysosome-related genes has also been reported 41 . The authors used 8 genes (RAMP3, GPLD1, FABP5, CD68, CSPG4, SORT1, CSPG5, CSF3R) to construct a risk model, and the study showed that the risk model could better predict the clinical outcome, and the higher the risk, the worse the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These findings reaffirm the significance of HDAC2 in controlling autophagy in HCC tumor cells. Meanwhile, 91 lysosome-associated differentially expressed genes (IFI30 [34] , HYAL2 [35] , HPS6, ARSB, WDR24 [36] , CSF3R [37] , FNIP2 [38] , ARSK and so on) were detected, demonstrating that HDAC2 can significantly enrich to lysosomal pathways (Fig 4B). As lysosomes are the primary executors of autophagy function [39] , we focused downstream targets of HDAC2 on lysosomal genes.…”
Section: Hdac2 Upregulates Laptm4b To Promote Autophagy and Autophagy...mentioning
confidence: 99%
“…Genes such as Receptor Activity Modifying Protein 3 (RAMP3) and CD68 Molecule (CD68) have shown signi cantly expressed in HCC based on machine-learning algorithms [13]. Overall, these genes are considered vital candidates for potential diagnostic markers in HCC clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, bioinformatic analysis and machine learning have emerged as increasingly promising strategies for comprehensive and indepth analysis of large datasets, such as transcriptome sequences, and interdisciplinary collaborations have been instrumental in advancing clinical therapeutic methods [2]. The advent of modern computerassisted medical science has provided signi cant guidance and hope for previously untreatable diseases, such as utilizing the XGBoost algorithm for HCC diagnosis [13]. To meet the demand for early diagnosis, numerous efforts have focused on developing new methods based on deep learning analysis [33].…”
Section: Introductionmentioning
confidence: 99%